2018
DOI: 10.1016/j.envint.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

WHO/ILO work-related burden of disease and injury: Protocol for systematic reviews of exposure to long working hours and of the effect of exposure to long working hours on stroke

Abstract: At least two review authors will independently screen titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. At least two review authors will assess risk of bias and the quality of evidence, using the most suited tools currently available. For Systematic Review 2, if feasible, we will combine relative risks using meta-analysis. We will report results using the guidelines for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 56 publications
1
41
0
2
Order By: Relevance
“…The adverse effects of long working hours on physical and mental health have been evidenced [22][23][24]. A high number of work hours was positively associated with burnout in the present study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The adverse effects of long working hours on physical and mental health have been evidenced [22][23][24]. A high number of work hours was positively associated with burnout in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…One study found a substantial correlation between the number of working hours per week and the frequencies of both musculoskeletal disorders and psycho-vegetative complaints [22]. Several studies have suggested a potential association of exposure to long working hours with increased risks of cardiovascular diseases in general, and coronary heart disease and stroke specifically [23]. A systematic review of epidemiological evidence revealed that long working hours are associated with a depressive state, anxiety, and sleep disorders [24].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumoconiosis is mainly attributed to occupational risk factors, and a minimum proportion of cases may be caused by the natural environment or second-hand exposures [13]. Significant differences in incidence stratified by sex were observed for pneumoconiosis, which emerged as a male-predominant condition in people older than age 20.…”
Section: Discussionmentioning
confidence: 99%
“…To optimize parameters used in estimation models, a systematic review is required of studies on the prevalence of exposure to long working hours ('Systematic Review 1'), as well as a second systematic review and meta-analysis of studies with estimates of the effect of exposure to long work hours on ischaemic heart disease ('Systematic Review 2'). In the current paper, we present the protocol for these two systematic reviews, in parallel to presenting systematic review protocols on other additional risk factor-outcome pairs elsewhere [6][7][8][9][10][11][12][13] . To our knowledge, this is the first systematic review protocol of its kind.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from Systematic Reviews 1 and 2 will be reported in two distinct journal articles. For all four protocols in the series with long working hours as the risk factor 6,10,11,14 , one Systematic Review 1 will be published.…”
Section: Introductionmentioning
confidence: 99%